ACCIDENTS IN ROAD TRAFFIC. RESEARCHES OF ROAD ACCIDENTS BY MEANS OF INSURANCE STATISTICS - D. V. Kapsky (Наука и техника)
The paper presents an analysis of the existing situation pertaining to road accidents in theRepublicofBelarus. A critical estimation of the indicators used in the statistical analysis is given and a new relative indicator of the general road accident involvement risk is offered in the paper. The paper considers data of insurance statistics which covers different damage aspects due to road accidents in the field of transport insurance as an alternative source.The paper provides basic statistical data on insurance statistics in theRepublicofBelarus. A private insurance company is taken as an example for an analysis of insurance payments. Conclusions have been made in respect of road traffic quality evaluation and theMinsk streetareas which are mostly subjected to road accidents are revealed in the paper. The paper determines practical scientific and scientifically-methodical targets for improvement of road safety.